Restricted human activities shift the foraging strategies of feral pigeons (Columba livia) and three other commensal bird species. (January 2021) - Soh, Malcolm C.K.; Pang, Roanna Y.T.; Ng, Breyl X.K.; Lee, Benjamin P.Y.-H.; Loo, Adrian H.B.; Er, Kenneth B.H.
Abstract: Invasive species are a growing concern with increasing global connectivity. Feral pigeons ( Columba livia ) are widespread and invasive, thus their effective control is of keen international interest. The COVID-19 pandemic has offered an unprecedented opportunity to investigate the impact of a nation-wide Circuit Breaker (restricted human activities) in Singapore on first, the abundance of the feral pigeons and three urban commensals—the Javan myna ( Acridotheres javanicus ), common myna ( A. tristis ), and house crow ( Corvus splendens ) in different food source types; and second, the activity budgets of feral pigeons. A significant and progressive decline in feral pigeon abundance was observed in open food centres and feeding hotspots after the Circuit Breaker was implemented. While the house crow and common myna were less affected, the Javan myna abundance increased moderately at refuse collection centres during the Circuit Breaker and decreased significantly in green spaces after the Circuit Breaker. Changes in food abundance could also predict changes in feral pigeon abundance and its effect was greatest in feeding hotspots. A greater proportion of feral pigeons was observed foraging and moving with a smaller proportion seen resting with probable consequences on their reproductive capacity. Our study also cautions against drawing inferences on biological responses due to similar social restrictions without careful consideration of other ecological factors, like average flock size and time of the day, which also affected the proportion of pigeons foraging on natural versus anthropogenic food. In summary, our results advocate a food limitation approach to control the feral pigeon populations. Highlights: Pest bird abundances declined during COVID-19 with feral pigeons most affected. Limiting anthropogenic food supply can drastically reduce feral pigeon abundance. More pigeons were foraging and moving with less resting during the pandemic. Feral pigeon flocks that foraged more on natural food sources were smaller. Food limitation is vital in controlling invasive pest bird populations.